PANDANGAN KEPALA KUA TERHADAP PEMERIKSAAN PERNIKAHAN PEREMPUAN BERCADAR PASCA PMA NO 30 TAHUN 2024 PERSPEKTIF KESADARAN HUKUM SOERJONO SOEKANTO - Wardana, Andhena Wisnu; Izzuddin, Ahmad (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
Marriage is sunnatullah which is the basis for human survival, and is regulated by religious and state laws. In Indonesia, regulations related to marriage registration are regulated in the Regulation of the Minister of Religion No. 30 of 2024, which covers marriage registration procedures, including the examination of marriage files. One of the interesting aspects to be studied in the regulation is article 6 which requires the removal of all face barriers when examining marriage files, then what about women who wear veils, which has the potential to pose challenges in identity validation. This study aims to analyze the views of the Head of KUA regarding the Regulation of the Minister of Religion No. 30 of 2024 in KUA, Kedungkandang District, Malang City in the examination of marriage files for veiled women. The research method used is a qualitative approach with the type of empirical research, collecting data through structured interviews with the Head of KUA and analysis of related documentation. The results of the study show that the implementation of these regulations often faces challenges in terms of legal interpretation and cultural sensitivity. The Head of KUA in Kedungkandang District tends to prioritize a balance between administrative fulfillment and respect for religious rights and personal freedom without having to override existing regulations, even though there are differences of opinion among the relevant officials. These findings provide important insights into the implementation of laws that are inclusive and sensitive to the cultural and religious diversity of Communities.